Development of CO2 snow cleaning for in situ cleaning of µCMM stylus tips - Feng, Xiaobing; Kinnell, Peter K.; Lawes, Simon (IOP Publishing, 2016)
Contamination adhered to the surface of a µCMM stylus tip compromises the measurement accuracy of the µCMM system, potentially causing dimensional errors that are over ten times larger than the uncertainty of a modern µCMM. In prior work by the authors, the use of a high pressure CO2 gas stream was demonstrated to achieve significant cleaning rate for a range of contaminant without damage to the stylus tip surface. This paper explores the practical challenges of achieving effective stylus tip cleaning in situ on µCMM systems. Two types of snow cleaning approaches were evaluated for their coverage of cleaning, thermal impact and gas flow forces. This work then presents a novel multi-nozzle prototype system using pulsed snow streams to achieve cleaning coverage over the entire stylus tip, and balances forces from the snow streams reducing drag force imparted by the gas stream to levels comparable to the probing force of µCMMs, as well as allowing automated cleaning procedure integrated into a µCMM system.